PENGARUH RASIO KEUANGAN TERHADAP KEBIJAKAN DEVIDEN (STUDI PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Aniyati, Lisma; Setyono, Hendro (Jurnal Fokus Manajemen Bisnis, 2020)
This researchÂ aimed to analyze and test the effect of financial ratios of the dividendÂ policy on the real estate and properties listed in the Indonesia Stock Exchange. TheÂ independent variables is used Return On Investment (ROI), Debt to TotalÂ Assets (DTA),Â EarningÂ PerÂ ShareÂ (EPS),Â andÂ TotalÂ AssetÂ Turnover (TATO). Another dependent variable is used dividend Payout Ratio (DPR). The populationÂ ofÂ thisÂ research is 50 companies. ThereÂ areÂ from theÂ real estate companies and propertiesÂ which registeredÂ in Indonesia Stock Exchange in theÂ periodÂ 2012-2014.Â BecauseÂ notÂ allÂ membersÂ ofÂ theÂ populationÂ isÂ meetÂ the criteria,Â theÂ samplingÂ methodÂ isÂ usedÂ purposiveÂ samplingÂ methodÂ thereÂ areÂ 9 samples.Â TheÂ analyticalÂ methodÂ areÂ usedÂ theÂ classicÂ assumptionÂ testÂ and regression test. Based on the survey results showingÂ thatÂ fromÂ partially there is onlyÂ DTA variablesÂ wereÂ notÂ significantlyÂ influentÂ toÂ theÂ dividendÂ policyÂ onÂ realÂ estatecompanyÂ and propertiesÂ which registeredÂ in IndonesiaÂ Stock Exchange. Another variableÂ areÂ ROI, EPS, and TATOÂ wereÂ significant effectÂ toÂ the dividend policy on real estate and properties which registered in Indonesia Stock Exchange. TheÂ resultsÂ simultaneousÂ testÂ showedÂ theÂ ROI,Â DTA,Â EPS,Â andÂ TATO variablesÂ hasÂ anÂ influenceÂ toÂ theÂ realÂ estateÂ companyÂ andÂ propertiesÂ which registered in indonesian Stock Exchange. TheÂ higherÂ coefficient of determination is 49.10%.